2015
DOI: 10.1590/1234-56781806-94790053s01010
|View full text |Cite
|
Sign up to set email alerts
|

A Eficiência das Explorações Leiteiras Micaelenses (Açores)

Abstract: Resumo:A discussão no âmbito da Política Agrícola Comum marca a atualidade açoriana. Um cenário possível é o decréscimo de apoios, subsídios à quota leiteira, aos produtores açorianos. Para compensar esta quebra de rendimento urge que os produtores leiteiros melhorem a eficiências das suas empresas agrícolas. Este trabalho tem como objetivo conhecer os valores de eficiência e estimar o número de explorações eficientes em S. Miguel, ilha que contribui com 75% da produção regional. A produção de leite dos Açores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The CAP and water legislation both limited the competitiveness in the Alentejo region with impacts only mitigated by uptake of new technologies for production (Dos Santos et al, 2012). On the other hand, Almeida and Silva (2015), investigating the efficiency framework for the Azorean milk farms under the CAP reforms and using data from several sources including farm data within a data envelopment analysis methodology, found that the Azorean milk farms needed to improve their technical efficiency and that subsidies helped increase the number of farms. Regarding competitiveness, Avillez (2015) reported that after joining the European Economic Community, Portuguese agriculture had an interesting framework in terms of economic results and competitiveness that worsened after the second half of the 1990s.…”
Section: Synthesis Of Evidencementioning
confidence: 99%
“…The CAP and water legislation both limited the competitiveness in the Alentejo region with impacts only mitigated by uptake of new technologies for production (Dos Santos et al, 2012). On the other hand, Almeida and Silva (2015), investigating the efficiency framework for the Azorean milk farms under the CAP reforms and using data from several sources including farm data within a data envelopment analysis methodology, found that the Azorean milk farms needed to improve their technical efficiency and that subsidies helped increase the number of farms. Regarding competitiveness, Avillez (2015) reported that after joining the European Economic Community, Portuguese agriculture had an interesting framework in terms of economic results and competitiveness that worsened after the second half of the 1990s.…”
Section: Synthesis Of Evidencementioning
confidence: 99%